2006
DOI: 10.1364/ao.45.000489
|View full text |Cite
|
Sign up to set email alerts
|

Correction method for absorption-dependent signal enhancement by a liquid-core optical fiber

Abstract: The enhancement of a dissolved chemical's Raman scattering by a liquid-core optical fiber (LCOF) geometry is absorption dependent. This dependence leads to a disruption of the usual linear correlation between chemical concentration and Raman peak area. To recover the linearity, we augmented a standard LCOF Raman spectroscopy system with spectrophotometric capabilities, permitting sequential measurements of Raman and absorption spectra within the LCOF. Measurements of samples with identical Raman-scatterer conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…For the PLS regression analysis, the regression vectors for prediction are constructed by employing the number of loading vectors which corresponds to the minimum error in inner cross-validation in the calibration data set. In all cases, the number of factors is observed to vary between 4 and 7, which ensures that the rank of the calibration model is more than three times smaller than the size of the calibration data set [26]. Finally, the LS-SVM computations are performed using a LS-SVM MATLAB toolbox [27].…”
Section: Methodsmentioning
confidence: 99%
“…For the PLS regression analysis, the regression vectors for prediction are constructed by employing the number of loading vectors which corresponds to the minimum error in inner cross-validation in the calibration data set. In all cases, the number of factors is observed to vary between 4 and 7, which ensures that the rank of the calibration model is more than three times smaller than the size of the calibration data set [26]. Finally, the LS-SVM computations are performed using a LS-SVM MATLAB toolbox [27].…”
Section: Methodsmentioning
confidence: 99%
“…LCOFs greatly enhance the number of scattered photons that can be collected over a given integration time, with the additional advantage of requiring a small sample volume in the order of 1 µL [23]. Building on the work of Altkorn et al [24,25], the experiments of Qi and Berger [19,23,26,27] demonstrated the application of LCOFs for multicomponent analysis. An illustration of the LCOF Raman system used by Qi and Berger in 2007 [27] for quantifying different analytes in blood serum and urine samples is given in Fig.…”
Section: A Optical Systems For Multicomponent Analysis With Raman Spmentioning
confidence: 99%
“…1; detailed information can be found in previous publications. 20,24,26 Briefly, the biofluid sample resides within the LCOF and is illuminated sequentially by an 830 nm laser L and a broadband thermal source W through fiber OF 1 . Backscattered Raman and transmitted white-light spectra are recorded over the same wavelength range by a spectrograph and CCD detector.…”
Section: A Instrumentationmentioning
confidence: 99%
“…In previous studies, we found the approaches gave similar values of s . 26 Here we calculated s by optimizing predictions of blood urea nitrogen (BUN) in blood serum samples and urine urea nitrogen (UUN) in urine samples, arriving at values of 0.005 and 0.007 mm Ϫ1 , respectively. The same optimized s value was then used for all the chemicals in the sample set; i.e., s was not a free parameter for each chemical.…”
Section: Data Processingmentioning
confidence: 99%
See 1 more Smart Citation